Nutrition in paediatric intestinal failure - Theodoric Wong (World Nutrition Journal, 2023)
Children with irreversible intestinal failure can survive and lead good quality of life in the recent 20-30 years. A lot of this advance is due to better understanding of what and how to deliver nutrition (both enterally and parenterally) effectively. This talk aims to provide not only an overview but some practical considerations on how to manage paediatric intestinal failure.